2017
DOI: 10.1515/hsz-2017-0249
|View full text |Cite
|
Sign up to set email alerts
|

The role of microRNAs in chronic respiratory disease: recent insights

Abstract: Chronic respiratory diseases encompass a group of diverse conditions affecting the airways, which all impair lung function over time. They include cystic fibrosis (CF), idiopathic pulmonary fibrosis (IPF), chronic obstructive pulmonary disease (COPD) and asthma, which together affect hundreds of millions of people worldwide. MicroRNAs (miRNAs), a class of small non-coding RNAs involved in post-transcriptional gene repression, are now recognized as major regulators in the development and progression of chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 191 publications
2
59
0
3
Order By: Relevance
“…10 In our study, the expression of miR-206 was upregulated in the lung tissues from COPD patients, which was a further confirmation on the previously study showing the upregulation of miR-206 in the plasma of COPD patients. 10 In our study, the expression of miR-206 was upregulated in the lung tissues from COPD patients, which was a further confirmation on the previously study showing the upregulation of miR-206 in the plasma of COPD patients.…”
Section: Discussionsupporting
confidence: 91%
“…10 In our study, the expression of miR-206 was upregulated in the lung tissues from COPD patients, which was a further confirmation on the previously study showing the upregulation of miR-206 in the plasma of COPD patients. 10 In our study, the expression of miR-206 was upregulated in the lung tissues from COPD patients, which was a further confirmation on the previously study showing the upregulation of miR-206 in the plasma of COPD patients.…”
Section: Discussionsupporting
confidence: 91%
“…MicroRNAs (miRNAs) play important roles in regulating gene expression and specific miRNAs participate in the fibrotic process in different tissues and organs . MiRNA‐155 (miR‐155), a pro‐inflammatory factor via SHIP‐1 downregulation, has been identified as having immune regulatory functions and plays a critical role in tissue fibrosis in liver and lung .…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) play important roles in regulating gene expression and specific miRNAs participate in the fibrotic process in different tissues and organs. [7][8][9] MiRNA-155 (miR-155), a pro-inflammatory factor via SHIP-1 downregulation, has been identified as having immune regulatory functions and plays a critical role in tissue fibrosis in liver and lung. [10][11][12][13] However, contradictory effects of miR-155, pro-fibrotic and anti-fibrotic, in experimental and idiopathic pulmonary fibrosis, have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs have been recognized as important regulators in the gene regulation of COPD. 7 Downregulated miR128 in smokers, downregulated miR181d and miR30a-3p in COPD lung tissue, and increased miR223 in lungs of smokers have been demonstrated. 7 In a study investigating muscle wasting of COPD patients, the results showed that increased miR424-5p was associated with muscle wasting.…”
Section: Introductionmentioning
confidence: 97%